The Influence of Tax Dispute Resolution Mechanisms: Legal Contributions of Tax Consultants and Tax Attorneys in Indonesia - Silalahi, Heriantonius; Maulana, Nandi; Ana, Lenny; Kurnia, Budi (Yayasan Ilomata, 2025)
This study examines the roles of tax consultants and tax attorneys in resolving tax disputes in Indonesia, emphasizing their contributions to tax compliance, dispute resolution, and litigation. As tax regulations become increasingly complex, taxpayers encounter significant challenges in understanding and fulfilling their tax obligations, mainly when disputes arise with the Directorate General of Taxes. The involvement of tax professionals is essential in mitigating risks, ensuring compliance, and navigating intricate legal frameworks. Despite extensive research on tax compliance and litigation as separate subjects, limited studies explore the complementary functions of tax consultants and attorneys in the Indonesian context. This paper addresses this gap by analyzing their collaborative roles in providing advisory services, representing clients in disputes, and safeguarding taxpayer rights. This study uses a qualitative research methodology to review relevant tax regulations and incorporates insights from interviews with tax professionals. The findings reveal that tax consultants primarily assist in tax planning, compliance, and dispute prevention, while tax attorneys focus on legal representation and advocacy in tax litigation. Their collaboration is instrumental in minimizing financial penalties, expediting dispute resolution, and enhancing taxpayer confidence. Strengthening the synergy between these professions can lead to a more effective tax administration system, fostering fairness, legal certainty, and improved taxpayer trust in Indonesia’s tax regime.